Tour d’horizon des activités de Sodarcan en 1993 - Parizeau, Robert (Assurances, 1994)
Sodarcan is the largest Canadian independently-owned holding company operating in insurance brokerage, actuarial services and employee benefits consulting, and reinsurance brokerage, through a group of professionally autonomous subsidiaries. Sodarcan inc, aims to: • Provide the Group' s clients with top-quality, professional services through competent and dedicated employees who are constantly encouraged to broaden their horizons. • Continue to grow in targeted markets so as to maintain each subsidiary' s position as a major participant in Canada while, where applicable, developing progressively in selected markets outside the country. • Ensure, through its diversified operations, the stability of the Group' s consolidated financial performance while providing its shareholders with a return at least comparable to the industry average. Here are large excerpts of the shareholders' message given on May 11, 1994 by Mr. Robert Paizeau.